2019
DOI: 10.1515/jbcpp-2019-0153
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac autonomic modulation in response to stress in normotensive young adults with parental history of hypertension

Abstract: BackgroundHypertension is the major health burden associated with increased cardiovascular morbidity and mortality. Positive family history and stress are the risk factors for hypertension. The present study aims to evaluate the effect of acute stress on the cardiac autonomic modulation in normotensive individuals with parental history of hypertension.MethodsSixty healthy male volunteers (30 with parental history of hypertension-NTPH+ group and 30 without parental history of hypertension-NTPH− group) in the ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Of the HRV studies, 14 included only men [15–17,20,22–25,27,32,33], four included both sexes [9,14,26], and no HRV study included only women. HRV was measured through ECG [9,17,20,23–26,32,33] or heart rate monitor [14–16,22,27], with 5-min [17,20,23,24] to 30-min [33] analyses. Table 1 shows the main characteristics of selected studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the HRV studies, 14 included only men [15–17,20,22–25,27,32,33], four included both sexes [9,14,26], and no HRV study included only women. HRV was measured through ECG [9,17,20,23–26,32,33] or heart rate monitor [14–16,22,27], with 5-min [17,20,23,24] to 30-min [33] analyses. Table 1 shows the main characteristics of selected studies.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty [8,15–20,22,27,31,33,35,37–39,41] and 34 studies [8–28,31–33,36,37,39–42] reported body mass and BMI data, respectively. Some studies were matched according to body mass or BMI to a control group FHH − [12,40].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations